Studies on Hexokinases in Potato (Solanum tuberosum L.) by In silico and Biochemical Approaches - Mittal, Chestha (My University, 2023)
Potato is one of the most significant tuber crops in terms of nutrition and consumption. It has a promising role in world in terms of food security. The process of tuberization is governed by several TFs and is susceptible to variable temperatures. This indicates the economical and scientific importance of tuber formation for further research. A number of biotechnological and genetic techniques can be used to understand the complex process of tuberization and associated biochemical pathways in order to increase potato yield. Hexokinase (EC 2.7.1.1), an allosteric enzyme belongs to the phosphor-transferases family. It is one of the crucial and rate limiting enzymes involved in the conversion of sucrose to hexose-phosphates during the stolon-to-tuber transition of potatoes. The formation of G6P in presence of HXK is responsible to interconnect various important carbohydrate metabolic pathways. In this study, enzyme extraction and assay were performed from various harvested organs of five potato cultivars. It primarily focusses on the comparative study of HXK isoforms and their functions applying various bioinformatic tools. Genome wide study revealed 6 HXK genes localized on 6 chromosomes. The multiple sequence alignment along with the phylogenetic analysis was performed to study the conserved patterns of HXKs in various plant species. Crucial motifs with their functions were retrieved and analysed. Protparam tool was used to predict various physico-chemical properties of HXK. This study would be useful to study the regulation of HXK enzyme in Indian potato cultivars. It would provide insights on the involvement of HXK in the maturation of plant organs. This would help in the right approach for genetic manipulations to raise transgenics with high HXKs activity in various cultivars of potato to satisfy the future global nutritional demands.
M.Sc. Biotechnology thesis
Keywords: Potato (Solanum tuberosum L.); Tuberization; Hexokinases (HXKs); Sequence analysis; Organ extracts; HXK activities